Studi Petrografi dan Alterasi Batuan Diabas Sebagai Wall-Rock pada Daerah Pationgi Kecamatan Patimpeng, Kabupaten Bone, Sulawesi Selatan (Jurnal Geomine, 2019)
Administratively, the research area Pationgi Region, District of Patimpeng, Province of South Sulawesi, lying between 04o54’00" – 04°56’00" South Latitude and 120°10'00" - 120°12’00" East Longitude. This study aims to determine the characteristic of diabase as the wall-rock in the study area and to determine the range of temperature and depth of formation. Detail field geological mapping serve as a main method in to determine the geomorphology, stratigraphy and structural geological condition. Detail sampling collection campaign is conducted to collect samples in the field and followed by detail petrographic analyses using Nikon polarisation microscopic. The wall-rock consists of mainly pyroxene and plagioclase, showing a typical of diabasic texture. Based on the petrographic analyses, it is shown that the alteration mineral occurs as clay mineral-chlorite-quartz-sericite and carbonate minerals. These mineral assemblages indicated that the alteration zone developed in this area is argillic zone. The mineral assemblages also show that the mineralization temperature range from 100 0C – 150 0C within 0 – 50 meter below the surface.